Where did they hide my presents? silly dilly Christmas songs - Katz, Alan (Aladdin Paperbacks, 2005)
Well-known Christmas songs, including "O Christmas Tree" and "Deck the Halls," are presented with new words and titles, such as "Toy Catalogs" and "At the Mall."